DAMPAK SOSIAL PERBEDAAN PENDAPAT DALAM PENENTUAN AWAL RAMADHAN DAN 1 SYAWAL TERHADAP UMAT ISLAM DI KOTA SEMARANG - Suhanah Suhanah (Harmoni, 2012)
This article is a case study on the social effect on difference on determining the beginning of Ramadhan and Syawal toward moslem community in Semarang. The research is qualitative in terms of methods. Formal and religious leaders say that there is no problem about the differences. In fact there never conflict among moslem community. However there are some small family unrest in the forms of arguing of the difference among family members. Parents and children celebrate in different date, where parent follow the govenrment announcement, as the children celebrate which is based on a Moslem organization. The meaning of celebrating lebaran is quite lost and there is no togetherness among the family members.